Efektivitas program self-compassion untuk meningkatkan resiliensi individu dewasa awal - Yuwono, Albertus Christian; Yudiarso, Ananta (Procedia : Studi Kasus dan Intervensi Psikologi, 2024)
COVID-19 pandemic has been ongoing for more than 2 years and it had a lot of bad effect towards any people. This phenomenon requires someone to have a stronger adaptability to rise and live in the situation that changed extremely and drastically. In this kind of situation, self compassion as a concept of acceptance that someone can gave to theirselves regardless of how external condition, can be one of the solution for this phenomenon. Based on this, researchers are interested in seeing the effectiveness of the self-compassion program (SCP) to increase a person's resilience (a person's strength to recover from problems). Researchers provide scales during the pre-test and post-test in this program. There were 20 participants (N=20) aged between 18-25 years (early adulthood). The intervention in this study was a self-compassion program (SCP). Resilience measurements were carried out using the Resilience Scale for Adults. Data was analyzed using stacking and racking methods using the Winstep application. The results of the analysis showed that there was an increase in participants' resilience after SCP was carried out. The research results also showed that there was an increase in internal and personal resilience factors. Pandemi COVID-19 telah berlangsung selama lebih dari 2 tahun dan membawa banyak dampak buruk bagi siapa pun. Fenomena ini menuntut seseorang untuk memiliki kemampuan adaptasi yang lebih kuat untuk bangkit dan hidup dalam situasi yang berubah secara ekstrem dan drastis. Dalam situasi seperti ini, self-compassion sebagai sebuah konsep penerimaan yang dapat diberikan seseorang terhadap dirinya sendiri, apapun kondisi eksternalnya, dapat menjadi salah satu solusi atas fenomena tersebut. Berdasarkan hal tersebut peneliti tertarik untuk melihat efektivitas self-compassion program (SCP) dalam meningkatkan resiliensi seseorang (kekuatan seseorang untuk pulih dari permasalahan). Peneliti memberikan skala pada saat pre-test dan post-test pada program ini. Partisipan berjumlah 20 orang (N=20) berusia antara 18-25 tahun (dewasa awal). Intervensi dalam penelitian ini adalah self-compassion program (SCP). Pengukuran resiliensi dilakukan dengan menggunakan Skala Resiliensi Dewasa. Data dianalisis dengan metode stacking dan racking dengan menggunakan aplikasi Winstep. Hasil analisis menunjukkan adanya peningkatan resiliensi peserta setelah dilakukan SCP. Hasil penelitian juga menunjukkan adanya peningkatan faktor resiliensi internal dan pribadi.